A Study on Marriage Practices and Changes in Nepalese Society: A Case Study of Namobuddha Kavray - Acharya, Suresh (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
“Marriage practices and its changes” research done at Namobuddha, Kavray Marriage is a socially supported union involving two or more individuals. Marriage practices are influenced by various factors which bring changes in these marriage practices. Here in this research on the marriage practices today and their changes throughout the years. The main objective of this research was to understand the changes in marriage practices. It focuses on influence of modernization, globalization, and technological advancement on marriage practices in Nepalese society. The descriptive research design was used for data collection. We used schedule questionnaire, face to face interview and observation method for collecting responses of sample. Altogether, there were 50 samples that were selected randomly based on the purpose of the study. In this study, we found slow changes in marriages practices because of the role of education, media, technology, empowerment, and modernization. Many people have married at their legal age with a minimum age gap and without any pressure from family. They also have registered their marriage, and both the spouses take the important decision of their family.